An isoflavone-enriched diet alleviates Parkinson’s disease in mice by inhibiting ferroptosis through gut microbiota-mediated serotonin production - Yang, Le; Ma, Yan; Wang, Haiying; Xie, Likai; Yu, Yan (Frontiers in Immunology, 2026)
ObjectiveParkinson’s disease (PD) is a severe neurodegenerative disorder whose pathogenesis is closely linked to gut microbiota dysregulation. However, whether and how modulation of gut homeostasis can ameliorate PD remains unclear. Dietary isoflavones have been associated with neuroprotective effects and show strong potential in shaping the composition of the gut microbiota, yet their underlying mechanisms in PD are poorly understood.MethodsMicrobiomics and non-targeted metabolomics were utilized to characterize microbial community composition and metabolic alterations in the MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-induced mouse model of PD. Subsequently, both the MPTP-induced PD mouse model and in vitro cell experiments were employed to investigate the effects and underlying mechanisms of the differentially regulated metabolite serotonin on PD pathogenesis.ResultsHere, we show that an isoflavone-enriched diet alleviates motor deficits and dopaminergic neuron loss in an MPTP-induced mouse model of PD. This protective effect is mediated via a gut–brain axis mechanism: isoflavones promote the expansion of intestinal Lactobacillus species, especially Lactobacillus intestinalis, leading to increased 5-hydroxytryptamine (5-HT) production in both serum and brain. Elevated 5-HT activates central 5-HT1A receptor (5-HTR1A), which in turn triggers downstream PI3K-AKT signaling to suppress ferroptosis—a key pathogenic process in PD. Pharmacological inhibition of either 5-HTR1A or the PI3K-AKT pathway abolishes the neuroprotective effects of 5-HT.ConclusionsOur findings reveal a novel dietary-microbiota-serotonergic pathway that mitigates ferroptosis and neurodegeneration, highlighting the therapeutic potential of isoflavone-based interventions for PD.